2010
DOI: 10.1186/1471-2164-11-116
|View full text |Cite
|
Sign up to set email alerts
|

Genomic sequencing and analyses of Lymantria xylina multiple nucleopolyhedrovirus

Abstract: BackgroundOutbreaks of the casuarina moth, Lymantria xylina Swinehoe (Lepidoptera: Lymantriidae), which is a very important forest pest in Taiwan, have occurred every five to 10 years. This moth has expanded its range of host plants to include more than 65 species of broadleaf trees. LyxyMNPV (L. xylina multiple nucleopolyhedrovirus) is highly virulent to the casuarina moth and has been investigated as a possible biopesticide for controlling this moth. LdMNPV-like virus has also been isolated from Lymantria xy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 79 publications
1
25
0
1
Order By: Relevance
“…4B and C), indicating that Ld109 was capable of suppressing apoptosis and caspase-3-like A database search revealed that ld109 homologues were found in nine NPVs, four granuloviruses, and one poxvirus. The Ld109 protein shared amino acid sequence identities ranging from 23.3% with fowlpox virus FPV217 (1) to 86.0% with Lymantria xylina MNPV ORF109 (22). A domain search revealed no characteristic domains of the Ld109 protein that were linked to possible functions, and functional analyses have not been conducted for any of these Ld109 homologues.…”
mentioning
confidence: 99%
“…4B and C), indicating that Ld109 was capable of suppressing apoptosis and caspase-3-like A database search revealed that ld109 homologues were found in nine NPVs, four granuloviruses, and one poxvirus. The Ld109 protein shared amino acid sequence identities ranging from 23.3% with fowlpox virus FPV217 (1) to 86.0% with Lymantria xylina MNPV ORF109 (22). A domain search revealed no characteristic domains of the Ld109 protein that were linked to possible functions, and functional analyses have not been conducted for any of these Ld109 homologues.…”
mentioning
confidence: 99%
“…Later, the phylogenetics of NPVs were generated with other conserved genes, www.scienceasia.org for example lef-2 33 , lef-8, lef-9 34,35 , and ecdysteroid UBP-glycosyl transferase (egt) 4 . Recently, many phylogenetics of NPVs have been established by means of the combination of several conserved gene sequences and whole genome sequences 7,36,37 . These phylogenetic trees were suggested to be more acceptable than those constructed by a single gene.…”
Section: Phylogenetic Analysis Of Group Imentioning
confidence: 99%
“…The remaining 4 unique amino acid positions were located in the C-terminal region of IE-1. The C-terminal region contains a domain required for inhibitory and DNAbinding activities 37 . Only one of these 4 unique amino acid positions was in a putative single-stranded-DNAbinding motif that may be involved in DNA binding 12 .…”
Section: Phylogenetic Analysis Of Group Imentioning
confidence: 99%
See 1 more Smart Citation
“…helicase, que desenrola as fitas de DNA; dna polimerase, polimeriza a nova fita de DNA; lef-3, que produz uma proteína ligante (estabilizadora) à fita simples de DNA, KUZIO et al, 1999;LI et al, 2002a;NAI et al, 2010). Durante a replicação, as proteínas ALK-EXO (nucleases alcalinas), LEF-3 e VLF-1 atuam no processo de recombinação, permitindo montar mais rapidamente os genomas virais .…”
Section: Replicação Do Dnaunclassified